Factors influencing the use and consumption of brown rice in Chinese restaurants. Issue 1 (1st January 2016) - Liu, Ting; Wang, Xiaochun; Marquart, Len
ABSTRACT: The objective of this study was to examine factors influencing current use and consumption of brown and white rice in Chinese restaurants. Thirty Chinese restaurants were selected from the Twin Cities metro area to participate in the study. Face-to-face or phone interviews, based on a questionnaire, were conducted with a manger/owner of each restaurant. Plate waste observations were used to examine consumption for brown rice consumers ( n = 200) and white rice consumers ( n = 153) in a chain-Chinese restaurant. Data were analyzed using a t -test and analysis of variance. Results indicated that in 15 of the total restaurants, both brown and white rice were served. The main motivator for serving brown rice was to attract health conscious consumers, while low customer request was the major constraint for non-use. Authentic/family owned restaurants were less likely to serve brown rice than chain restaurants. Brown rice (85%) consumption was significantly higher than white rice (79%; P = .02), based on an average serving size of 8.7 oz. These results suggest that the availability of brown rice in restaurants increases consumption among brown rice eaters.